Ewing's sarcoma of the maxilla in an adolescent male - A rare case report - Manisha Lakhanpal Sharma; Siddharth Srivastava; Mansimranjit Kaur Uppal; Garima Martolia (Wolters Kluwer Medknow Publications, 2022)
Ewing's sarcoma (ES) is an atypical malignant neoplasm of long bones rarely affecting the head and neck region. Here, we report a case of a 13-year-old male patient with a chief complaint of an unhealed socket and swelling in the right mid-facial region, following an extraction. Intraoral examination revealed an unhealed socket with respect to permanent maxillary right second molar region. Advanced imaging such as cone-beam computed tomography (CBCT) revealed an aggressive, expansive, osteolytic lesion involving the right posterior maxillary alveolus, extending into the maxillary sinus. Histopathology and tumor markers such as the cluster of differentiation (CD)99 were deterrent in the diagnosis.